Effect of Early Skin-To-Skin Contact Intervention By Nurses on Physiological Stability Mother and Baby in RSIA Mutiara Bunda Padang - Nelwetis; Ni Nyoman Murti (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Skin-to-skin contact is an essential early intervention that supports physiological stability in mothers and newborns during the immediate postnatal period. Although its benefits are well documented, consistent implementation in perinatal nursing practice remains limited. Purpose: This study aimed to evaluate the effect of early skin-to-skin contact interventions performed by nurses on the physiological stability of mothers and newborns at RSIA Mutiara Bunda Padang. Methods: A quantitative study with a quasi-experimental pre–post test design was conducted involving 20 mother–infant pairs who received skin-to-skin contact for 60 minutes after delivery. Maternal physiological parameters included heart rate and body temperature, while newborn parameters included body temperature, respiratory rate, and heart rate. Data were analyzed using descriptive statistics and paired t-tests with a significance level of 0.05. Results: The findings showed improved physiological stability following the intervention. Newborn body temperature increased significantly from 36.5°C to 37.2°C (p < 0.05), indicating better thermal regulation. Maternal heart rate decreased significantly from 95 bpm to 85 bpm (p < 0.05), reflecting improved physiological adaptation. Bivariate analysis confirmed a significant effect of early skin-to-skin contact on physiological stability in both mothers and newborns (p < 0.05). Conclusion: Early skin-to-skin contact interventions by nurses are effective in improving maternal and neonatal physiological stability and should be integrated as a standard practice in postnatal care.